Implementasi Etika Bisnis Islam pada Pelaku Usaha Mikro, Kecil, dan Menengah (UMKM) di Kabupaten Kudus - Sudarsono, Sudarsono (Sharia Faculty Islamic Economic Law Study Department, 2022)
This study aims to examine business practices carried out by micro, small and medium enterprises (UMKM) in the Kudus Regency area using an Islamic business ethics approach. Islamic business ethics is measured through five principles, namely the principles of monotheism, honesty, benefit, responsibility, and justice. The research method uses descriptive qualitative approach to symbolic interaction. Collecting data using observation and interview techniques as well as using data analysis techniques Miles and Huberman. The results of the study show that Islamic business ethics have not been fully implemented by UMKM actors in Kudus Regency. As for there are several obstacles or obstacles in the application of the principles of Islamic business ethics for UMKM actors in running their business.